The Distribution of HLA-system Antigens in Children with Peptic Ulcer - T.V. Sorokman; M.-O.V. Popeliuk (Zaslavsky O.Yu., 2015)
In order to establish the features of HLA-system antigens distribution, their interlocus and intralocus combinations in peptic ulcer in children, all investigated patients (n = 120) and individuals from the control group (n = 100) underwent HLA-typing test of DRB1, DQA1 and DQB1 genes using the method of sequence-specific probe, amplification with sequence-specific primers. Peptic ulcer is associated with the specificities of DRB1*11, DRB1*13, allelic variant DQB1*0401/02, genotype DQB1*0301,0302 and haplotypes DRB1*07/DQA1*0301, DRB1*13/DQA1*0501, DRB1*11/DQB1*0501, DQA1*0102/DQB1*0401/02. Specificity DRB1*15, allele variant DQB1*0201, genotype DQB1*0301,0301 and haplotypes DRB1*15/DQA1*0101, DRB1*15/DQA1*0102, DRB1*01/DQB1*0201, DRB1*15/DQB1*0301, DQA1*0101/DQB1*0201, DQA1*0201/DQB1*0201 determine the resistance to peptic ulcer.